2011
DOI: 10.1111/j.1752-699x.2011.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bovine colostrum on viral upper respiratory tract infections in children with immunoglobulin A deficiency

Abstract: This is the first study to evaluate the effect of bovine colostrum in IgA-deficient children, and no adverse effects were observed. However, further studies are needed to confirm the efficacy and safety of bovine colostrum in IgA-deficient patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 24 publications
(42 reference statements)
0
52
0
Order By: Relevance
“…The immunoglobulins, lactoferrin and cytokines in colostrum are reported to show strong antiviral activity [56]. However, a double-blind, placebocontrolled study to evaluate the effect of BC on viral upper respiratory tract infections in IgA-deficient children failed to demonstrate a difference between salivary IgA levels between the control and test group, although the BC group did record a lower infection severity score [57]. Such studies remain to be conducted in similar adult patients along with elucidation of relevant mechanisms although the ones given below could be at work.…”
Section: Viral and Bacterial Illnessesmentioning
confidence: 90%
“…The immunoglobulins, lactoferrin and cytokines in colostrum are reported to show strong antiviral activity [56]. However, a double-blind, placebocontrolled study to evaluate the effect of BC on viral upper respiratory tract infections in IgA-deficient children failed to demonstrate a difference between salivary IgA levels between the control and test group, although the BC group did record a lower infection severity score [57]. Such studies remain to be conducted in similar adult patients along with elucidation of relevant mechanisms although the ones given below could be at work.…”
Section: Viral and Bacterial Illnessesmentioning
confidence: 90%
“…Our results were in agreement with previous reports. [3,1821] Uchida et al [19] demonstrated that ingestion of BC (6 to 7 days postpartum) significantly reduces the mean frequency of URTI and days of illness with fever in 3- to 6-year-old children compared with the placebo group. In a double blind, placebo-controlled, randomized trial, Brinkworth and Buckley [20] retrospectively pooled data from several previous studies examining self-reported URTI symptoms in 174 healthy adult males receiving BC or a whey-protein-based control supplement.…”
Section: Discussionmentioning
confidence: 99%
“…After BC therapy, the percentage reduction in the number of episodes of URTI from baseline was 73.01%, 83.25%, and 91.19% at 4, 8, and 12 weeks, respectively. Patıroğlu and Kondolot [3] studied the administration of an oral lozenge containing 14 mg of colostrum and 2.2 mg of lysozyme or a placebo lozenge 3 times per day for 1 week in 31 children aged 5 to 16 years with known IgA deficiency and clinical signs of URTI. The presence of viral infection was determined clinically, and etiologies were not confirmed by laboratory investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, some studies have observed increases in resting salivary SIgA concentration or output after colostrum supplementation whereas others have not. [141][142][143][144][145][146][147] Bovine colostrum supplementation has also be shown to reduce or blunt the increase in intestinal permeability induced by heat stress or the administration of non-steroidal antiinflammatory drugs (NSAIDs, which are known to have detrimental effects on the gut). [148][149][150] As previously mentioned, in vitro (and ex vivo) markers of immune function are valuable to help identify potential mechanisms of action but in vivo and clinically relevant markers are more valuable.…”
Section: Dairy-derived Supplements or Functional Foods (Probiotics Bmentioning
confidence: 99%